KEBANGKITAN SUNNISME ABAD XI - Syathori, Ahmad (PUTIH: Jurnal Pengetahuan Tentang Ilmu dan Hikmah, 2016)
The period of 'Abbasid caliphate rule according to Nourouzzaman Shiddiqi, is divided into two periods, the uphill period that began from its establishment to the al-Watsiq (842-847 H), the ninth caliph of the' Abbasid dynasty; then the declining period that starts from the caliph al-Mutawakkil to the caliph al-Mu'tashim, the thirty-seventh caliph. This period of government was marked by the Mongol invasion of 1258 AD. The periodization according to Nourouzzaman Shiddiqi is in line with other historians that despite differing opinions in terms and the number of periodisasinya, but almost all agree that the beginning of the decline of 'Abbasid dynasty was when the government held by the caliph al-Mutawakkil. The fundamental reason why the reign of al-Mutawakkil is considered as the beginning of decline, each having a different opinion. There is a reason that when al-Mutawakkil took office, he began to widen the influence of the intervention of people who came from Turkey. In addition, some argue that in the time of al-Mutawakkil officially taqlid and taslim attitude applied. There is much more speculation of historians in view of the causes of the 'Abbasid dynastic decline. From the time of the Caliph al-Makmun (198-218 H / 813-833 AD) to the time of the caliph al-Watsiq (842-847 AD) the Mu'tazilah dominated the government so that the government issued a decree of Mihnah (inquisition). Mihnah is a wisdom done by the caliph al-Makmun about the enactment of the examination or more precisely said coercion to his people against the acceptance of the doctrine of the Koran is a creature. This event is carried out using political power, even by force. In the discourse of the debate of the doctrine of Islamic teachings, rationalist circles throughout history contrasted with those who think scripturally. The first group is supported by the Mu'tazilah, while the second-sided flow is fully supported by the hadith scholars (Ahlussunnah). With the support of the rulers, the Mu'tazila can impose its flow on society. Mihnah (Inquisition) is the official institution in launching its movement. It is narrated in the historical literature that the victims of violence during the Mihnah period were the experts of hadith. They force those who cling to the opinion of the hadith who claim that the Qur'an is qadim. Most of the scholars of hadith were finally forced to agree with them, only one figure who insisted on his opinion, he was Ahmad Ibn Hanbal (720 - 855 AD) who remained at his stance even though he was punished.